Outwit, Outlast, Outplay: Survival Techniques (for Teachers and Students) in the Large Language Classroom - Lobalsamo, Teresa; Victoriano-Martínez, Ramón A. (Nouvelle Revue Synergies Canada)

(untitled) (University of Guelph, School of Languages and Literatures, 2016)
What once began as experimental has now become a trend whereby large classes (50 students or more) are the norm. Language classes, where a small student body is ever more preferred, is also part of the same growing movement. Literature tells us, however, that students feel the larger the size of the class, the more negatively it will affect their ability to learn; yet, universities are reluctant to provide the small classes that are essential for an effective and organic learning environment. The following paper provides readers with 1. a brief summary of the research conducted on the effectiveness or otherwise of large classes; 2. practices that the authors have found to be most effective for the successful delivery of a large language class - practices which can also be implemented in lectures with fewer students.